2021
DOI: 10.1186/s12871-021-01294-w
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetics may modulate cancer surgical outcome: a possible role of miRNAs regulation

Abstract: Background microRNAs (miRNAs) are single-stranded and noncoding RNA molecules that control post-transcriptional gene regulation. miRNAs can be tumor suppressors or oncogenes through various mechanism including cancer cell biology, cell-to-cell communication, and anti-cancer immunity. Main Body Anesthetics can affect cell biology through miRNA-mediated regulation of messenger RNA (mRNA). Indeed, sevoflurane was reported to upregulate miR-203 and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 179 publications
0
13
0
Order By: Relevance
“…A study of lung cancer also demonstrated the direct effect of opiates on cancer progression ( 23 ). The underlying molecular mechanisms remain elusive but it may be involved with the target receptors of opioids and downstream signaling pathways, induced by microRNAs’ modification ( 24 ). MOR overexpression promoted hepatocellular carcinoma cell proliferation and metastasis ability through EMT signaling pathway ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study of lung cancer also demonstrated the direct effect of opiates on cancer progression ( 23 ). The underlying molecular mechanisms remain elusive but it may be involved with the target receptors of opioids and downstream signaling pathways, induced by microRNAs’ modification ( 24 ). MOR overexpression promoted hepatocellular carcinoma cell proliferation and metastasis ability through EMT signaling pathway ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…-Inhibition of HIF-1α protein synthesis induced by hypoxia [80]; -Inhibition of the mRNA expression of MMP-2 and MMP-9 and p38 MAPK signaling (signaling pathway regulating proliferation, cell motility, and survival) [81]; -Inhibition of the NF-κB pathway [82]; -Downregulation of S100A4 in endothelial cells and suppression of VEGF expression from cancer cells with consequent anti-angiogenic effects [83,84]; -Upregulating miRNA expression (tumor suppressors and by inhibiting the expression of miRNAs that works as oncogenes) [85]; -Inhibiting histone acetylation [86].…”
Section: Anesthetic Agents Volatile and Intravenous Anestheticsmentioning
confidence: 99%
“…There are more than 1500 miRNA molecules in human body, and miRNAs play critical roles in various cell biology ( 73 , 74 ). Variations of miRNA expression may affect cancer cell activity and lead to tumor recurrence and metastasis ( 75 , 76 ). Studies have reported that sevoflurane suppresses breast cancer cell proliferation by upregulating miR-203 ( 77 ).…”
Section: Effects Of Sevoflurane and Propofol On Microenvironments Of Breast Cancer Cellsmentioning
confidence: 99%